2018
DOI: 10.7554/elife.32833
|View full text |Cite
|
Sign up to set email alerts
|

Distinct myocardial lineages break atrial symmetry during cardiogenesis in zebrafish

Abstract: The ultimate formation of a four-chambered heart allowing the separation of the pulmonary and systemic circuits was key for the evolutionary success of tetrapods. Complex processes of cell diversification and tissue morphogenesis allow the left and right cardiac compartments to become distinct but remain poorly understood. Here, we describe an unexpected laterality in the single zebrafish atrium analogous to that of the two atria in amniotes, including mammals. This laterality appears to derive from an embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 71 publications
4
30
1
Order By: Relevance
“…At 26hpf hapln1a expression is upregulated on the 176 left side of the cardiac tube with elevated levels of expression of hapln1a in the future atrium 177 compared to the future ventricle, recapitulating the regionalised ECM expansion we observe 178 in the heart (compare Fig 2E and Fig 1K). This is in line with recent studies demonstrating that 179 the posterior compartment of the cardiac disc is re-positioned to the left side of the heart tube 180 (Guerra et al 2018). By 50hpf hapln1a expression is restricted to very low levels in the 181 atrioventricular canal, the precursor to the atrioventricular valve ( Fig 2F).…”
Section: Ecm Expansion 154supporting
confidence: 87%
See 3 more Smart Citations
“…At 26hpf hapln1a expression is upregulated on the 176 left side of the cardiac tube with elevated levels of expression of hapln1a in the future atrium 177 compared to the future ventricle, recapitulating the regionalised ECM expansion we observe 178 in the heart (compare Fig 2E and Fig 1K). This is in line with recent studies demonstrating that 179 the posterior compartment of the cardiac disc is re-positioned to the left side of the heart tube 180 (Guerra et al 2018). By 50hpf hapln1a expression is restricted to very low levels in the 181 atrioventricular canal, the precursor to the atrioventricular valve ( Fig 2F).…”
Section: Ecm Expansion 154supporting
confidence: 87%
“…Analysis 343 of meis2b mutants revealed defects in atrial morphology at juvenile and adult stages, supporting 344 our conclusion that early anterior-posterior asymmetry in the heart disc/left-right asymmetry 345 in the heart tube are important for continual cardiac morphogenesis. However, contrary to our 346 study which reveals a reduced atrial size in hapln1a mutants, meis2b mutant adult zebrafish 347 exhibit an enlarged atrium (Guerra et al 2018) suggesting that while they are expressed in the same domain, these two genes regulate atrial morphogenesis differently. hapln1a mutants are 349 adult viable (data not shown), therefore it would be interesting to determine whether the atrium 350 remains underdeveloped in hapln1a mutants, or whether they also develop a hyperproliferative 351 atrial hypertrophy phenotype by adulthood.…”
contrasting
confidence: 75%
See 2 more Smart Citations
“…These facts indicate that the Tbx5 ‐Hh network is important for atrial septum formation though Tbx5‐downstream targets, such as Gas1 , Osr1 , and Cdk6 (Xie et al., ; Figure b,c). Furthermore, a recent study demonstrated that in zebrafish, the species with no cardiac septum, transcription factor meis2b shows an expression pattern restricted to the left side of the atrium, and this expression pattern is important for establishment of atrial asymmetry through regulation of pitx2c expression (Guerra et al., ). These facts indicate that the molecular blueprint exists even under the situation without cardiac septation, and the genes that show restricted expression are important for establishment of atrial asymmetry and septation.…”
Section: Coevolution Of Atrial Septum and Lungmentioning
confidence: 99%